2016
DOI: 10.1111/age.12424
|View full text |Cite
|
Sign up to set email alerts
|

Targeted high‐throughput growth hormone 1 gene sequencing reveals high within‐breed genetic diversity in South African goats

Abstract: This study assessed the genetic diversity in the growth hormone 1 gene (GH1) within and between South African goat breeds. Polymerase chain reaction-targeted gene amplification together with Illumina MiSeq next-generation sequencing (NGS) was used to generate the full length (2.54 kb) of the growth hormone 1 gene and screen for SNPs in the South African Boer (SAB) (n = 17), Tankwa (n = 15) and South African village (n = 35) goat populations. A range of 27-58 SNPs per population were observed. Mutations resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…At least two studies have shown that the Tankwa goat is closely related to other indigenous goat breeds (e.g. Boer and South African village goats) and has similar genetic diversity (Kotze et al, 2014;Ncube et al, 2016). Kotze et al (2014) compared the Tankwa goat with commercial breeds such as Boer, Angora, and Saanen goats, and concluded that the Tankwa goat is a unique genetic resource that needs to be managed optimally.…”
Section: Introductionmentioning
confidence: 99%
“…At least two studies have shown that the Tankwa goat is closely related to other indigenous goat breeds (e.g. Boer and South African village goats) and has similar genetic diversity (Kotze et al, 2014;Ncube et al, 2016). Kotze et al (2014) compared the Tankwa goat with commercial breeds such as Boer, Angora, and Saanen goats, and concluded that the Tankwa goat is a unique genetic resource that needs to be managed optimally.…”
Section: Introductionmentioning
confidence: 99%
“…Morrison [9] described the Northern Cape Speckled, Mbuzi/Nguni, and the Eastern Cape Xhosa Lob ear as the indigenous veld goat populations that are kept by the Indigenous Veld Goats (IVG) association farmers in organized farming and breeding societies that are usually under semi-intensive production systems. Additionally, there are uncharacterized village ecotypes that are raised by communal farmers that have not been developed for any traits and that have multipurpose functions, i.e., for their meat, milk, and skin [7,10]. The carcass quality characteristics of Indigenous Veld Goats (IVG) and village goats have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The primary role of goats in African countries is meat (chevon), which serves as a source of easily accessible protein for poor communities [10]. Although chevon has excellent meat quality characteristics and health benefits, it is the least preferred among consumers, which is mainly due to unfavourable perceptions that are related to toughness and strong odour [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used RNA-Seq data to investigate differential gene expression in the pituitary of South African Boer and Village goats that were raised under different production systems. The study hypothesised based on the growth rates, meat yield and meat quality analysis from previous studies ( Ncube et al, 2016 ; Ncube et al, 2022 ) that the South African Boer goats raised intensively will be associated with upregulation of genes that promote higher growth rate and meat yield while downregulation of growth promoting genes would be expected in the village goats raised extensively.…”
Section: Introductionmentioning
confidence: 99%